Dengue fever presenting with cerebellitis: A case report - Santhirasekaram Sathees; Deepa Amarasekara; Pubudu Jayasekara; Peumini Rajapakse; L.F. Sumaiya (Asian Pacific Journal of Tropical Medicine)
Rationale: Dengue fever is a mosquito-bome viral infection, which commonly presents as an acute febrile illness. As the number of cases increases, rare manifestations including neurological manifestations are occasionally encountered. Patient concerns: A 20-year-old female presented with fever for 3 days with slurring of speech and unsteady gait, which were developed from the third day of illness. On examination, she had bilateral cerebellar signs. Dengue non-structural protein 1 antigen and dengue IgM in serum were positive. Her cerebrospinal fluid analysis and magnetic resonance image brain were normal. Diagnosis: Dengue cerebellitis. Intervention: Supportive management with fluids including oral rehydration solutions and intravenous fluids and paracetamol. Outcome: Cerebellar symptoms and signs completely resolved by the 20th day of illness. Lesson: Dengue cerebellitis is an unusual neurological manifestation of dengue infection.